Coffee Grounds Waste Valorization into Natural Antioxidant Extracts for Food Preservation - Fatimah Azzahra Hasibuan; Steven Suryoprabowo; Eddy Seong Guan Cheah (International Journal of Food Sciences and Nutrition Innovations, 2026)
Background: Coffee grounds are one of the largest types of organic waste generated daily by the food and beverage industry. Although commonly discarded, used coffee grounds still contain valuable bioactive compounds, especially phenolic compounds, which have strong antioxidant properties. Utilizing coffee waste as a source of natural antioxidants can reduce environmental problems caused by organic waste while providing an alternative to synthetic food preservatives.Aim: This study aims to utilize used coffee grounds by extracting natural antioxidant compounds using an ethanol–water solvent mixture and evaluating their potential as natural preservatives to extend food shelf life.Method: This review paper employed a systematic literature review approach to collect and analyze scientific studies published between 2019 and 2025 related to the valorization of spent coffee grounds (SCG) into natural antioxidant extracts for food preservation. Literature searches were conducted using scientific databases, including Scopus, Web of Science, ScienceDirect, PubMed, and Google Scholar, using keywords such as “spent coffee grounds,” “coffee waste valorization,” “phenolic compounds,” “natural antioxidants,” “food preservation,” “ethanol-water extraction,” and “bioactive compounds.”Result: The extraction process produced coffee ground extracts containing phenolic compounds with antioxidant activity. Previous studies have demonstrated that coffee ground extracts can inhibit undesirable chemical reactions in food and contribute to extending food shelf life.Conclusion: Used coffee grounds have potential as a sustainable source of natural antioxidants and food preservatives. Their utilization can reduce organic waste, support environmentally friendly food preservation methods, and promote the implementation of a circular economy in the food industry.